Perencanaan ruang terbuka hijau sebagai penampung burung di kawasan pesisir Pantai Lima, Mengwi, Badung - Bryantara, I Putu Agus Octa; Yusiana, Lury Sevita; Yuni, Luh Putu Eswaryanti Kusuma (Jurnal Arsitektur Lansekap, 2019)
Green open space planning as a bird sink in Lima coastal area, Mengwi, Badung. The Reduction of bird breeding habitat caused the bird population decreases every year. Birds have its ecological functions as part of the food chain and ecosystem balancer, bioindicators of environmental change, help pollinate the plants and as a pest predators. The survey method used is observation, interviews and literature reviews. The planning stages refer to Simond (1983) consist of objectives, inventory, analysis, synthesis and planning. The purpose of Lima Coastal Areas Planning is as a sink area. The results of data analysis showed the suitability of the Lima Coastal area as a green open space bird habitat with an area of 18,000 m2 has various types of birds such as turtle birds, erasian sparrows, peking bondol, cow swallow, turtledoves, cucumber merbah, rice kareo birds, rice fields and heron. Green space planning for bird habitats in the Lima Coastal area is arranged based on the concept of green open space as a sink area for birds. Spatial planning based on its function is divided into storage areas, transitions, corridors and education areas. The circulation systems are the circulation of birds from the source area to the sink area and the human circulation. Vegetation Planning also needed as a source of feed, nest and breed. Site Planning can be prepared as a bird green space sink in accordance with the sink and source concept so that it can be developed into a core area of sink protection, transition, corridor and education area.